PREFERENSI KONSUMEN TERHADAP EMPAT VARIETAS UNGGUL MANGGA INDONESIA BERDASARKAN RESPON EMOSI - Rizqi Sofi Nur Fitriyah; Christofora Hanny Wijaya; Budi Nurtama (Jurnal Teknologi dan Industri Pangan, 2021)
Understanding the consumer preferences and needs for new products is really important to support the acceptance and marketing success of a product. This study associated the preferences with emotional responses to various ready-to-eat and fresh food products. The objective was to obtain the preference based on emotional responses from different superior mango cultivars named agri gardina 45 (AG), gadung 21 (GD), red garifta (GM) and orange garifta (GO). The preference profile was measured by the 9-point hedonic scale, while the emotional response by EsSense25 combined with rating questionnaire and 5-point scale. This study involved 108 panelists. The finding showed that consumers liked gadung and orange garifta, while slighlty liked agri gardina and red garifta. Additionally, the EsSense25’s response showed that 4 out of 25 emotional terms were significantly different among the cultivars, namely happy, joyful, satisfied, and disgusted. However, fifteen attributes among the 25 emotion terms strongly correlated with liking, with the strongest terms on joyful, happy, satisfied, interested, secure, and free. These six emotions were associated with garifta orange, one of the newly released cultivars. The results suggested that garifta orange is potentially well-accepted and commercialized widely.